FINANCIAL STATEMENTS BASED ON INFORMATION TECHNOLOGY IN A VILLAGE OWNED BUSINESS ENTITY WEST BANDUNG REGENCY - Ilyas, Supriyanto; Yusuf, Paulus Sugianto; Susiani, Rini, Syafdinal; Novianto, Robertus Ary; Hardika, Andika Linggar, Islahuzzaman (CENTRAL ASIA AND THE CAUCASUS, 2022)
Village-owned business entity based on Indonesian Government Regulation No 11 of 2021, must make an accountability report that includes financial statement two times a year and must be reported to the interested party. Village-owned business entities have several problems making a financial report because of improper recording and knowledge to create a financial reporting. Management officials of village-owned enterprises have not been able to apply information technology to make financial reports. This study aims to train and socialization of financial statements based on information systems to a village-owned business entity.